Editorial - Nakata, Martin; Mackinlay, Elizabeth (The Australian Journal of Indigenous Education, 2014)
The quest to improve Indigenous people's access, participation and outcomes in education wherever we live in the world involves a concerted effort from all, and across all levels of education from the pre-school to the postgraduate sector. Improvements in these areas, as we have seen in past issues of The Australian Journal of Indigenous Education, are closely tied to improving other social and economic indicators in Indigenous lives, such as health, employment, governance and housing. The importance of research in the field of Indigenous education is a fundamental part of understanding the complexity of the issues, the level of constraints, as well as the many possibilities as we move forward in time. And, as practitioners of Indigenous education continue to keep looking for new ideas or examples of teaching and learning practice, AJIE continues to invite descriptions of educational practice and articulations of Indigenous experience from our readership. As educational research and practice have progressively become global, we have sought experiences beyond our Aeotorea/New Zealand and North American colleagues to countries and contexts that are less familiar to us. We are pleased to report that for our efforts in this regard, AJIE is now listed with SCOPUS, the largest abstract and citation database of peer-reviewed literature.